Emotional Intelligence and Employee Performance: A Study of Teachers in Secondary Schools in Benue State, Nigeria - Juliet Abeyi Otor; Terungwa P. T. Jato (Universitas Medan Area, 2023)
The study's goal was to look into the impact of emotional intelligence on teacher performance in secondary schools in Makurdi, Benue State, Nigeria. The study was based on the theory of emotional intelligence as propounded by Daniel Goleman in 2002. It adopted a descriptive survey research design. The sample comprises 160 secondary school teachers and administrators from 15 schools. A structured questionnaire was used to collect relevant data. Descriptive and regression analyses were used in the analysis. The paper's theoretical review is based on Goleman's works (2002). Four emotional intelligence constructs (self-awareness, self-management, social awareness, and relationship management) were used, as were the study's objectives. The findings revealed a link between emotional intelligence and secondary school teachers’ performance. It is recommended, among other things, that the concept of emotional intelligence be clearly inculcated in the recruitment and selection criteria of secondary school teachers.